Nurse managers’ perspectives on nurses’ performance in mentorship program - Aung, Khin Thandar; Jamal, Nor Qurratul Ain (Elsevier Inc, 2018)
Objective: The aim of this study was to explore the nurse managers’ perspectives on nurses’ performance in a mentorship program. Method: A cross-sectional survey was conducted on 51 nurse managers in Hospital Tengku Am- puan Afzan (HTAA), Kuantan, Pahang, by using modified and self-developed questionnaire with the Cronbach’s alpha value 0.994. The data were analyzed by using descriptive statistics such as central tendency, frequency and percentage. Results: The gender of respondents was predominantly female (100%). The mean age is 45.41 (SD ± 4.51). In terms of level of education, the majority of the respondents (76.5%) were having a diploma. The majority has been in practice as a staff nurse between 11 to 20 years, and most of them have been practicing as nurse managers for about five years and less. Meanwhile, re- sults showed that the nurse managers had positive perceptions upon newly graduated nurses’ performance in the mentorship program, concerning on their effective communication, profes- sional development and creative thinking. Conclusions: It is vital to identify the effectiveness of the mentorship program among nurses; hence, it enhances job satisfaction among new nurses.